2014
DOI: 10.3109/09273948.2014.945600
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Keratitis in Rheumatoid Arthritis Patients

Abstract: The characteristics of HSK in patients with RA differed from HSK in immunocompetent patients. The stromal keratitis cases were very aggressive and difficult to manage, with perforation and gram-positive bacterial co-infection as frequently associated conditions. Prophylactic therapy at standard doses was unsuccessful to avoid recurrences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…23 Immunosuppressive agents used in rheumatoid disease (Table 3, cases 6 and7) could also have played a role in HSK reactivation. 24…”
Section: Discussionmentioning
confidence: 99%
“…23 Immunosuppressive agents used in rheumatoid disease (Table 3, cases 6 and7) could also have played a role in HSK reactivation. 24…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in India reported a notably higher incidence of bilateral HSV keratitis, up to 25% of all herpetic keratitis cases [13]. Higher bilateral rates have also been reported in pediatric patients [14] and in patients with immunosuppression or other underlying conditions [15,16]. Table 1 summarizes the incidence rates reported in literature.…”
Section: Epidemiologymentioning
confidence: 99%
“…PUK can pose a diagnostic dilemma in cases with immune system disorders, such as rheumatoid arthritis. Excluding infectious agents is mandatory for appropriate treatment [16,19,20].…”
Section: Clinical Presentationmentioning
confidence: 99%
See 2 more Smart Citations